Chasing peace : a story of breakdowns, breakthroughs, and the spiritual power of neuroscience - Rosshirt, Tom (The Open Field/Penguin Life, 2025)
A personal journey from debilitating anxiety and depression to peace through self-directed neuroplasticity, retraining the brain to unlearn harmful patterns and alight with spiritual principles to embrace our true self.